REGULATION OF THE EUKARYOTIC PROTEIN-SYNTHESIS BY PHOSPHORYLATION OF ELONGATION FACTOR-II - (:unkn) unknown (MBR PRESS INC, 1993)
The phosphorylation of elongation factor 2 (EF-2) by Ca2+/calmodulin kinase III decreases its activity and results in inhibition of translation. The effects of different experimental conditions on the phosphorylation of EF-2 in rabbit reticulocyte have been investigated. The phosphorylation of EF-2 was enhanced in the presence of GDP and inhibited by cyclic-AMP and NEM whereas the ADP-ribosylation of EF-2 did not change the extent of its phosphorylation.
Keywords: MR 100,000 SUBSTRATE; FACTOR-II; KINASE-III; INITIATION; IDENTIFICATION; ACTIVATION; EF-2; HEME